Pengelolaan Berkelanjutan Sumber Daya Ikan Cakalang (Katsuwonus pelamis) Di Perairan Selatan Prigi, Trenggalek, Jawa Timur Indonesia - Gatut Bintoro; Fetriyani Fetriyani; Wildan Al Farizi; Kristina Marsela; Wirastika Adihapsari; Lisa Nur Hidayah; Supriatna Supriatna; Andik Isdianto; Arief Setyanto; Agus Tumulyadi; Vian Dedi Pratama; Dewa Gede Raka Wiadnya; Tri Djoko Lelono; Aisyiyah Nurmarina Bestari (Samakia : Jurnal Ilmu Perikanan, 2025)
Prigi waters belongs to the Republic of Indonesia's fisheries management area (FMA 573), which includes the South Indian Ocean of the island of Java to Nusa Tenggara. The species of large pelagic fish occurring in Indonesian waters include tuna comprising: madidihang (Thnunnus albacares), bigeye tuna (Thunnus obesus), albacore (Thunnus alalunga), bluefin tuna (Thunnus maccoyii), long tailed tuna (Thunnus mackerel). The small species of tuna include Skipjack tuna (K. Pelamis), Euthynnus affinis and Auxis thazard caught by purse seine, gillnet, troll line and payang fishing gear. Research purposes were to estimate value of maximum sustainable yield (MSY), total allowable catch (TAC), maximum economic yield (MEY), and open access (OA), to suspect rate and status utilization of Skipjack tuna (K. pelamis). Data analysis in this research was convertion of fishing gear, surplus production model by Schaefer, Fox, and Gordon-Schaefer model. The results of the conversion analysis of fishing gears are determined using a standard fishing gear, which is troll line as fishing gear standard. Result showed that sustainable potential obtained catch and effort of Skipjack tuna (K. pelamis) in MSY condition around 810 ton/year and 2,020 trip/year, and in TAC condition 648 ton/year and 1,616 trip per year, while in bioeconmic analysis in MEY condition was 680 ton/year and 1211 trip/year so that a profit Rp. 4,136,008,186, and in OA condition around 778 ton/year and 2,423 trip/year where the profit obtained Rp. 0. Utilization rate of Skipjack tuna (K. pelamis) was 106% so that the status of the stocks categories was Over Exploited